Integrasi Nilai Pendidikan Islam dalam Program Rehabilitasi Sosial untuk Pemenuhan Hak Pendidikan dan Kemandirian Penyandang Disabilitas - Salmah, Syarifah; Shapiah, Shapiah (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2024)
Blind people are a vulnerable group. Much literature states that their economic level is still not prosperous. One of their needs is adequate housing. One of the efforts made by the Banjarbaru City Government is to lend decent housing in the same area on Jalan Trikora. This area is known as the Banjarbaru City complex for the blind. The forms of attention provided include adequate housing, compassion, skills training and fulfillment of other basic rights. The religious aspect is a priority emphasized by the Banjarbaru City Government for the residents of the complex. Ta'lim assembly activities, learning the Al Qur'an in braille, birthday activities are routinely carried out at this place. The adaptability of the residents has also been carried out well. Ability to adapt to progress over time. Adaptation or social mobility has also been implemented well. The residents in the complex are blind people. The use rights are granted for life to selected blind people in Banjarbaru City.